DOMESTIC VIOLENCE: A COMPARATIVE ANALYSIS BETWEEN ISLAMIC LAW AND LAW NO. 23/2004 ON THE ELIMINATION OF DOMESTIC VIOLENCE - Sri Agustina (JURISTA: Jurnal Hukum dan Keadilan, 2017)
This paper aims to find out how the forms of domestic violence according to Islamic Law and Law Number 23 of 2004 concerning PKDRT, as well as legal protection efforts against perpetrators of domestic violence. Based on the results of the study in Islamic Law, it explains that in any form of reason violence is not justified. Because there is no evidence that allows being rough and hard on the wife. The forms of domestic violence according to Islamic law include physical violence, physical violence, sexual violence and economic violence. Meanwhile, Law Number 23 of 2004 states that forms of domestic violence are physical violence, psychological violence, sexual violence, and domestic neglect. Legal protection efforts in Islamic law are by sending a third party, either a guardian from both husband and wife parties, or ahkam chosen by both families as a peacemaker. Meanwhile, Law Number 23 Year 2004 is to provide legal protection and security to the victim.